Allogeneic Hematopoietic Stem Cell Transplantation for PEX1-Related Zellweger Spectrum Disorder: A Case Report and Literature Review - Chen, Kai; Zhang, Na; Shao, Jing-Bo; Li, Hong; Li, Jie; Xi, Jia-Ming; Xu, Wu-Hen; Jiang, Hui (Frontiers in Pediatrics, 2021)
Zellweger spectrum disorder (ZSD) is a heterogeneous group of autosomal recessive disorders characterized by a defect in peroxisome formation and attributable to mutations in the PEX gene family. Patients with ZSD have profound neurologic impairments, including seizures, severe retardation, and dysmorphic features, and poor prognosis. Currently, there is no specific, effective treatment. Here, we investigated the effects of allogeneic hematopoietic stem cell transplantation (allo-HSCT) on PEX1-related ZSD. The suspected clinical proband was first diagnosed at the Department of Neurology of our hospital. The proband died soon after diagnosis, and his family was studied. We found that a brother had the same genetic alterations, and he was diagnosed with Infantile Refsum disease（IRD）as the mildest form of ZSD. We implemented treatment with allo-HSCT, at the request of the child’s parents. After transplantation, we observed significant improvements in the clinical manifestations, very-long-chain fatty acids, and brain MRI. The patient has recovered well and not showed any abnormal clinical manifestations after 2years of follow-up. We have achieved satisfactory short-term results in the treatment of ZSD-IRD with allo-HSCT. Long-term follow-up and observation will be performed to determine the long-term prognosis.